Way for operators to build the telecommunication big data ecology - Mi LIU; Haichuan YANG; Zhenhua LI (Dianxin kexue)
In the era of rapid development of big data,telecom operator has abundant big data assets and need to unlock the potential of huge data in pipelines through the innovation and development of big data services urgently.The construction of telecom big data ecosystem would help telecom operator solve the problems encountered in the development of big data services effectively and new value growth would be brought out.The target form and construction steps of telecom big data ecosystem were also clarified.